Deep sequencing of extracellular eDNA enables total biodiversity assessment of ecosystems - Shivakumara Manu; Govindhaswamy Umapathy (Ecological Indicators, 2023)
The global decline in biodiversity driven by anthropogenic factors necessitates biomonitoring of ecosystems. However, current approaches are limited to targeted detection of taxa and fail to capture the total biodiversity of ecosystems. We postulated that extracellular environmental DNA (eDNA) represents a genetic repertoire of all the life forms in an ecosystem, which can be retrieved by deep sequencing. The feasibility and effectiveness of this approach were tested through a spatiotemporal study in Chilika Lagoon, a large and biodiverse Ramsar wetland ecosystem in India. Extracellular eDNA was enriched from large-volume filtered water samples using lysis-free methods and over 10.96 billion extracellular eDNA fragments were sequenced from 16 PCR-free shotgun sequencing libraries. The taxonomic classification results show that organisms from all the domains of life, including the low-abundant non-microbial taxa, can be detected with high sensitivity for taxonomic families with representative genomes. Interestingly, despite Bacteria representing a large proportion (87%) of the taxonomically classified reads, Eukaryotes showed the highest taxonomic diversity (73%). Further, using incidence-based asymptotic richness analysis, the total taxonomic diversity of Chilika was estimated to be 1071 families across the tree of life, comprising approximately 799 families of Eukaryotes, 230 families of Bacteria, 27 families of Archaea, and 13 families of DNA Viruses. We also quantified the compositional changes using Bray-Curtis dissimilarity and showed that extracellular eDNA can resolve the broad-scale spatiotemporal variation of biodiversity across the tree of life. These results demonstrate that PCR-free deep sequencing of extracellular eDNA is an effective approach for taxonomic diversity assessment across the tree of life in large ecosystems. With the increasing genomic resources and decreasing sequencing costs, we foresee its widespread application to monitor future biodiversity loss and support conservation, restoration, and management efforts in the Anthropocene.